THE IMPACT OF EMOTIONAL INTELLIGENCE ON INTERPERSONAL COMMUNICATION IN ENGLISH LANGUAGE TEACHING (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
In modern language education, emotional intelligence has become an essential factor influencing the effectiveness of interpersonal communication between teachers and students. English language teaching requires not only linguistic competence but also emotional awareness, empathy, motivation, and social interaction skills. This article examines the impact of emotional intelligence on interpersonal communication in English language teaching from psychological and pedagogical perspectives. The study analyzes the role of emotional intelligence in classroom interaction, student motivation, communication effectiveness, conflict management, and language acquisition processes. The article also explores theoretical approaches proposed by Daniel Goleman, John D. Mayer, and Peter Salovey regarding emotional intelligence and interpersonal communication.